1993
DOI: 10.1200/jco.1993.11.7.1253
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship of epirubicin-based first-line chemotherapy for advanced breast cancer: a prospective randomized trial.

Abstract: This study validates prospectively the concept of a dose-response relationship for an anthracycline-based chemotherapy in previously untreated advanced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(26 citation statements)
references
References 28 publications
0
23
1
2
Order By: Relevance
“…The rationale for high-dose therapy is a dose-response relationship and optimal scheduling-which has been demonstrated for breast cancer by several uncontrolled and controlled studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). These observations have been questioned by other authors (16), but the data today strongly support the fact that an increased dose intensity will be translated into an increased response rate.…”
Section: Dose Responsecontrasting
confidence: 44%
“…The rationale for high-dose therapy is a dose-response relationship and optimal scheduling-which has been demonstrated for breast cancer by several uncontrolled and controlled studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). These observations have been questioned by other authors (16), but the data today strongly support the fact that an increased dose intensity will be translated into an increased response rate.…”
Section: Dose Responsecontrasting
confidence: 44%
“…All but one highlighted an advantage in terms of response rate in standard dose arms, but none of these assessed the true role of dose intensity. In fact, analysing data from three studies with more than 100 patients each, two (Tannock et al, 1988;Focan et al, 1990) did not report any data about total dose delivered, while in the third (Habeshaw et al, 1991), the significant increase in median dose intensity reported was associated with a significant increase in median total dose. A study conducted at the M.D.…”
Section: ~~~~~~~~~~~Discussion Doomentioning
confidence: 99%
“…Hryniuk and Bush (1991) first observed in a retrospective study the direct correlation between dose intensity and clinical outcome in advanced breast cancer. We are aware of at least 11 randomised trials that have prospectively explored the role of dose or dose intensity in advanced breast cancer (Tannock et al, 1988;Habeshaw et al, 1991;Carmo-Peirera et al, 1987;Hoogstraten et al, 1976;O'Bryan et al, 1977;Forastiere et al, 1982;Beretta et al, 1986;Hortobagyi et al, 1987;Ebbs et al, 1989;Becher et al, 1990;Focan et al, 1990). Seven of these, actually addressed the value of standard, or almost standard, doses of chemotherapy compared with low doses (Tannock et al, 1988;Habeshaw et al, 1991;Carmo-Peirera et al, 1987;Hoogstraten et al, 1976;O'Bryan et al, 1977;Forastiere et al, 1982;Focan et al, 1990).…”
Section: ~~~~~~~~~~~Discussion Doomentioning
confidence: 99%
“…Clinical trials in metastatic breast cancer, in which dose intensity of chemotherapy was the most important variable, have shown that the response rate to chemotherapy rises with increasing dose intensity (5)(6)(7)(8). More intensive treatments might also reduce the incidence of bone and visceral relapses and have a greater influence on survival.…”
Section: Introductionmentioning
confidence: 99%